80 GHz AlGaInAs/InP colliding-pulse mode-locked laser with high pulse power. (7th November 2016) - Zhao, Pengchao; Liu, Anjin; Zheng, Wanhua
Abstract: We theoretically analyze the impact of a saturable absorber (SA) length on the pulse power of a semiconductor mode-locked laser and find that in the range of the SA length from 1.5 to 7%, a laser with a longer SA can generate pulses with a higher power. Based on the simulation, we demonstrate a colliding-pulse mode-locked laser with an 80 µm SA. The device generates pulses at 80 GHz, with a pulse width of 1.75 ps, peak power of 188 mW, pulse energy of 0.33 pJ, and time–bandwidth product of 0.51. The results provide new possibilities for the design of high-repetition frequency high-pulse power mode-locked lasers.